The effect of chitosan concentration on flocculation efficiency microalgae Porphyridium cruentum (Rhodhophyta). Issue 1 (November 2021) - Endrawati, H; Widianingsih, W; Nuraini, RAT; Hartati, R; Redjeki, S; Riniatsih, I; Mahendrajaya, RT
Abstract: Porphyridium cruentum is a species of red microalgae belongs to the family Porphyridiophyceae, divisi Rhodophyta. P. cruentum contains a lot of nutrients which are very useful as functional food. The purpose of this research is to determine the effect of chitosan concentration on the flocculation efficiency of P. cruentum . In this study, there were two treatments, namely the concentration of chitosan and the time of flocculation with 3 replications. Chitosan used were 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 ppm. The flocculation efficiency were carried out at 10, 20, 30 and 40 minutes. The highest density was reached on the seventh day as amount 1720x10 4 cell/mL. The results showed that there was an effect of Chitosan concentration on flocculation efficiency (Anova two way; Fcount = 4.109; df (9; 80); p=0.01). In addition, there was an effect of flocculation time on flocculation efficiency (Anova two way, Fcount = 4.498; df (3;80)). Furthermore, there was an interaction effect between the chitosan concentration and the time of flocculation. (Anova two way; Fcount = 26.635; df (2;80)). The greater the value of chitosan concentration given the greater the value of flocculation efficiency.